A novel approach of improving battery performance and longevity of the developed electrically assisted triwheeler vehicle by implementing torque sensor technology - Al Rashid, Md Jaber; Rahman, Ataur T.A.; Siddique, Abu Raihan Mohammad; Azad, Akm M.M.Abdul Malek (© 2017 Hindawi Limited, 2018)
This article was published in the International Journal of Vehicular Technology [© 2017 Md. Jaber Al Rashid et al.] and the definite version is available at : http://doi.org/10.1155/2017/3757421 The Journal's website is at: https://www.hindawi.com/journals/ijvt/2017/3757421/